2020
DOI: 10.1016/j.amsu.2020.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Invasive maxillary aspergillosis in a patient with systemic lupus erythematosus: Case report

Abstract: Introduction Invasive aspergillosis (IA) is a fungal infection caused by Aspergillus species (spp.). Aspergillosis is the most common source of opportunistic fungal infection in humans. IA can cause serious complications related to high morbidity and mortality in immunocompromised patients. Presentation of case We report a case of a 22-year-old female with a chief complaint of having a hole in the roof of her mouth. She was diagnosed with SLE in 2009. She had been consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…The surgery for aggressive aspergillosis should be aggressive, involving not only the necrotic tissue, but also the surrounding healthy-looking tissues considering the rapid extension of infection by the Aspergillus hyphae. 7 Systemic therapy itself is not sufficient as it may not completely eradicate the fungal organisms. Maxillectomy is one of the aggressive surgery techniques that is often applied with or without orbital exenteration in aggressive fungal infection management.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The surgery for aggressive aspergillosis should be aggressive, involving not only the necrotic tissue, but also the surrounding healthy-looking tissues considering the rapid extension of infection by the Aspergillus hyphae. 7 Systemic therapy itself is not sufficient as it may not completely eradicate the fungal organisms. Maxillectomy is one of the aggressive surgery techniques that is often applied with or without orbital exenteration in aggressive fungal infection management.…”
Section: Discussionmentioning
confidence: 99%
“…Direct microscopy of specimens with Blankophor and Calcofluor is preferred. Hematoxylin eosin staining can help in identifying the fungal elements, and PAS/GMS are important to highlight the hyphae 7,12 . From CT findings, Slonimsky et al 21 showed that mucormycosis is associated with bilateral mucosal thickening of nasal and maxillary sinuses with bony dehiscence, and aspergillosis is associated with unilateral maxillary sinus mucosal thickening without bony dehiscence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations